HOW IS FIRM VALUE AFFECTED BY DEBT AND PROFITABILITY POLICIES? - suhono Suhono (Accounthink, 2021)
ABSTRACT This study aims to analyze whether debt policies and profitability have a partial or simultaneous effect on Firm Value in Manufacturing companies listed on the IDX in 2015-2019. The sample used in this study were 18 companies using purposive sampling. The statistical method used is the classical assumption test, multiple linear regression analysis, descriptive analysis, verification analysis, and hypothesis testing. The results of this study partially debt policy has no effect on firm value with t-test results of t-score -0.618 <ttable 1.984 and significant 0.538> 0.05 then profitability has a significant effect on firm value with t-test results of t-score 9.891> t-table 1.984 and significant 0.000 <0.05. Debt policy and profitability simultaneously have an effect on profitability with the results of the test f-score 50.259> f-table 3.09 and significant value of 0.000 <0.05.